Opinions of Social Studies Teacher Education Studentsabout the Impact of Environmental Education on EcologicalLiteracy - Durmuş, Esen; Kınacı, Müşerref Kübra (My University, 2021)
In the century we live in, the level of environmental awareness, environmental knowledge, and ecological literacy of Social Studies teacher education candidates is of great importance to raise individuals who possess high ecological culture and environmental sensitivity. The research was carried out with a phenomenological pattern from qualitative research methods. The study group of research was determined by criterion sampling, which is a purposeful sampling method. The study group consists of 15 teacher education students who studied in the Department of Turkish and Social Sciences Education, Department of Social Studies Education and took the environmental education course in a Faculty of Education at a university in Turkey during the 2019-2020 academic years. The research data was obtained through a semi-structured interview form. The research data were analyzed by the content analysis method and evaluated with a qualitative data analysis program. One of the most important results obtained from this research includes that Social Studies teacher education students correctly perceive the concepts of Environmental Education and ecological literacy overall. Also, it is seen that Social Studies teacher education students stated that Environmental Education can provide development in their cognitive, affective, and behavioral dimensions such as information and increased consciousness about resource consumption, environmental awareness and sensitivity, problem-solving, understanding about sustainability, positiveattitudes and behavioral development and changes and that will positively affect the ecological literacy levels of an individual. For this reason, the concepts of Environmental Education and ecological literacy should be emphasized because it is necessaryfor ecological literacy to be explained to the students and projects should be carried out accordingly
Keywords: Eğitim; Eğitim Araştırmaları; Coğrafya; Çevre Bilimleri